Vulneración del principio de proporcionalidad de la pena en las sanciones aplicadas por el delito de transporte ilegal de combustible - Figueroa Medina, Janina Lizbeth (2016)
This thesis has a theme: "VIOLATION THE PRINCIPLE OF PROPORTIONALITY OF THE PENALTY IN THE SANCTIONS APPLIED BY THE ILLEGAL FUEL TRANSPORT CRIME”. In the Constitution of the Republic of Ecuador in Article 76. Numeral 6. Manifest that “The law shall establish due proportionality between offenses and criminal, administrative or other". It is therefore with the existing fallacies in the Integral Penal Code, IPCO, in its Art. 265. "Storage, transport, packaging, marketing or illegal distribution of hydrocarbons in the border provinces, seaports, rivers or territorial sea".- The person who, in the border provinces, sea, river or territorial sea ports, store , transport, packaging, marketed or distributed without proper authorization, products derived from hydrocarbons including liquefied petroleum gas or biofuels, will be punished imprisonment of five to seven years. The same penalty will be punished in the case that don’t detect the presence of a legally authorized substance that additives fuels permit their identification or alter the original structure the means of transportation without the authorization of the entity of the State corresponding. For this reason it is necessary to emphasize that this research work addresses an important problem into the current legal reality, by the absence of proportional penalties to punish crimes committed in the illegal fuel. For that is this vulnerable constitutional rights. And also it is affecting the Ecuadorian society in different areas. We want to show with this research, is the diagnosis of the causes that affect in the commission of these unlawful acts violative of fundamental rights by legislators and their collaborators in our country. It seeks as the main objective once demonstrated this problem, reforming the Art. 265 of IPCO, adding a clause that establishes a sliding scale with which must be punished the crime of illegal oil traffic. As well as determine, how it affects the country's economy and development with tax evasion, those engaged to illegal transport of fuel and its derivatives, and with that effectively guarantee the enforcement of our rights recognized by the Constitution.